UPAYA PEDAGANG PELATARAN DI PASAR SETONO BETEK KEDIRI DALAM MENGAKSES MODAL UNTUK MENGEMBANGKAN USAHANYA - Dhiyan Septa Wihara; Poniran Yudho Leksono (UNIVERSITAS PGRI MADIUN, 2018)
This study aims to 1) Describe the characteristics of the merchants of the market in the setono betek kediri which includes age, education level, family burden and work experience dependent on the access of capital to develop their business, 2) to analyze the relationship between the characteristics of the merchant of the market in the setono betek kediri towards their capital access to develop their business .The population in this study were vegetables and food street vendors, amounting to 120 traders. The number of samples used was 55 respondents with sampling technique using Slovin formula. The analysis used is Chi Square is to see the relationship between traders characteristics with access to their capital in developing their business. The results showed that the age of traders has a relationship to access capital, this is evidenced by the value of perason chi square 0.000 <0.05. The level of education of traders is also associated with capital kases with pearson chi square value 0.001 <0.05. The number of dependents of family burden is related to access to capital with pearson chi square value 0.001 <0.05. The work experience of traders is related to their capital access in developing the business with pearson chi square value 0.005 <0.05.Key words : Age, education level, family burden, work experience, street vendors